Acute Dermal and Ocular Irritation Testing of Herbal Shampoos in New Zealand White Rabbits - Meka, Madhusudhan; Mutyala, Krishnaji Rao; Gadela, Radha; Seru, Ganapathy (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: The objective of the presented study is to evaluate the acute dermal and ocular irritation of herbal shampoos consisting of a mixture of plant extracts. Materials and Methods: Both studies performed using New Zealand white rabbits in accordance with HICS and OECD guidelines respectively. In the cutaneous skin irritation test, erythema, eschar or edema evaluated. In the ocular irritation study, corneal opacity, area of opacity, iris, chemosis and conjunctival redness were evaluated. Results: In the cutaneous skin irritation test, all three herbal shampoos (PS9, PS20, and LS17) showed no significant erythema, eschar, or oedema formation after 72 hr of exposure and did not meet any of the irritation classification requirements. According to the Harmonized Integrated Classification System (HICS), all three herbal shampoos are classified as “Non Irritant” based on acute cutaneous testing. In the ocular irritation study, after 1, 24, 48, and 72 hr of observation, the treated eye appeared normal. There were no symptoms of systemic toxicity in any of the animals during the acclimatization and post-treatment periods. The results did not meet the irritation classification requirements for categories 1, 2A, or 2B because the treated animals had corneal opacity of 0.00, iris lesions of 0.00, conjunctival redness of 0.00, and chemosis of 0.00. Based on ocular irritation studies, all three herbal shampoos are classified as “Not Irritant” by HICS. The body weights of all the animals were within the typical range of variation for this species, strain, and age. All of the animals gained weight towards the end of the experiments. Conclusion: The acute cutaneous and ocular irritation studies indicated that three herbal shampoos (PS9, PS20, and LS17) were not irritant to the rabbit skin or eyes, indicating that they can be used in humans without irritation to the skin or eye.
Keywords: Herbal shampoo; Ocular irritation; Acute dermal; New Zealand white rabbits; Erythema